Consumption trends and factors influencing customers' choices: A Quantitative Research at Fuel Stations Sector in Portugal - Daniel MAGUETA; Sónia ESTRELA; Erica VEIGA (Communications of International Proceedings, 2024)
Many companies engaged in fuel retail, whether fossil-based or electricity-based, seek to complement their offerings to their customers through convenience stores located at their fuel stations. This study aims to analyze the profile of consumers who visit those convenience stores at fuel stations, investigating the factors they value the most during the purchasing process and emphasizing the role that brands, as a strategic asset, may have in influencing consumer trust and purchasing decisions. The survey applied in this work shows that most respondents do not make convenience purchases at fuel station stores, and those who do mainly buy impulse items such as chocolates, candies, bottled water, and juices. Additionally, the results highlight that the price of fuel, trust in the brand, discount coupons, and fuel cards are the factors most valued by respondents. The estimated model also shows that the income variable is statistically significant, as an increase in household income increases the likelihood of consumers purchasing products at fuel stations.
Keywords: Consumer Behavior; Category Management; Brand Value.